2010
DOI: 10.1007/s10517-010-1007-z
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Esophagus: Evaluation of the Status of Epidermal Growth Factor Receptors (EGFR and HER-2) by Immunohistochemistry and in Situ Hybridization

Abstract: We performed a parallel evaluation of the status of epidermal growth factor receptors EGFR and HER-2 in tumor samples from 31 patients with squamous cell carcinoma of the esophagus. Hyperexpression of proteins was detected by immunohistochemical methods and gene amplification and other chromosome abnormalities were studied using FISH reaction. Evaluation of EGFR status showed that amplification of EGFR gene was present in 25% cases and chromosome 7 polysomy was detected in 29.2% cases positive by protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
1
11
2
Order By: Relevance
“…The present study revealed that EGFR protein expression was associated with ESCC dedifferentiation, whereas EGFR gene amplification was associated with advanced stage and lymph node metastasis. These data are consistent with the results of previous studies (14)(15)(16)(17)(18)(19). Furthermore, Nicholson et al (31) demonstrated that EGFR overexpression is correlated with prognosis in esophageal, head and neck, ovarian, cervical and bladder cancer.…”
Section: Egfr Amplification Egfr Protein ----------------------------supporting
confidence: 94%
See 2 more Smart Citations
“…The present study revealed that EGFR protein expression was associated with ESCC dedifferentiation, whereas EGFR gene amplification was associated with advanced stage and lymph node metastasis. These data are consistent with the results of previous studies (14)(15)(16)(17)(18)(19). Furthermore, Nicholson et al (31) demonstrated that EGFR overexpression is correlated with prognosis in esophageal, head and neck, ovarian, cervical and bladder cancer.…”
Section: Egfr Amplification Egfr Protein ----------------------------supporting
confidence: 94%
“…Previous studies also demonstrated that EGFR overexpression/gene amplification may be indicative of unfavorable parameters for ESCC (16,17). For example, Delektorskaya et al (18) reported that overexpression of the EGFR protein is significantly correlated with tumor intravascular invasion and depth of invasion, whereas EGFR gene amplification is associated with tumor dedifferentiation. Kitagawa et al (19) demonstrated a significant correlation between EGFR gene amplification and ESCC lymph node metastasis.…”
Section: Egfr Amplification Egfr Protein ----------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…The results may be associated with the lifestyle of the Kazakh ethnic group, such as longterm excessive consumption of smoked meat, fermented foods, alcohol and tobacco, spicy foods, and lack of vegetables and foods rich in vitamins (1,20). In the future, the most sensitive probes should be selected to improve the early diagnosis of EC using molecular pathological techniques (9,10,21).…”
Section: Discussionmentioning
confidence: 99%
“…Most tumors highly overexpress receptors for such growth factors, which make growth factors highly attractive as targeting moieties. The most commonly studied growth factor receptors hyperexpressed in tumor tissue are vascular endothelial growth factor receptor (VEGFr) [62][63][64][65] and endothelial growth factor receptor (EGFr) [66][67][68]. Recently it was shown on more than 1000 human biopsia samples that receptor for follicle-stimulating hormone (FSHr) [69], in healthy adult expressed only in gonades (testes and ovaria), is largely (in > 90% cases) overexpressed in the vascularization zone of nearly all types of malignant tumors, being another promise for a holy grail of universal tumor targeting approach.…”
Section: Nanoparticles For Cancermentioning
confidence: 99%